2022
DOI: 10.2478/jtim-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory factors driving atherosclerotic plaque progression new insights

Abstract: Coronary atherosclerosis is a chronic inflammatory disease that can lead to varying degrees of blood flow obstruction and a common pathophysiological basis of cardiovascular disease. Inflammatory factors run through the whole process of atherosclerotic lesions. Macrophages, T cells, and neutrophils play important roles in the process of atherosclerotic inflammation. Considering the evolutionary characteristics, atherosclerosis can be divided into different stages as early atherosclerotic plaque, plaque formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 127 publications
0
13
0
Order By: Relevance
“…CUP3 might regulate calcium ion uptake within cells, notably within mitochondria . Calcium ions play an instrumental role in myriad biochemical and signal transduction pathways. , Mitochondrial calcium levels influence ATP production, enzymatic activities, and, in certain instances, cellular death pathways. , Within the context of sepsis, impaired cellular stress responses and mitochondrial functions are well-established. CUP3 could be crucial in maintaining mitochondrial calcium homeostasis, thus safeguarding mitochondrial functionality.…”
Section: Discussionmentioning
confidence: 99%
“…CUP3 might regulate calcium ion uptake within cells, notably within mitochondria . Calcium ions play an instrumental role in myriad biochemical and signal transduction pathways. , Mitochondrial calcium levels influence ATP production, enzymatic activities, and, in certain instances, cellular death pathways. , Within the context of sepsis, impaired cellular stress responses and mitochondrial functions are well-established. CUP3 could be crucial in maintaining mitochondrial calcium homeostasis, thus safeguarding mitochondrial functionality.…”
Section: Discussionmentioning
confidence: 99%
“…The Tag SNPs selection principles were as follows 24 : (1) Minimum allele frequency (MAF) >0.05, r 2 > 0.8. (2) SNPs reported to be associated with inflammation in the literature is preferentially selected. (3) SNP located in promoter and exon region is preferentially selected.…”
Section: Tag Snps Selection Of Il12bmentioning
confidence: 99%
“…In recent years, accumulating studies indicated inflammation are closely related to the progression of CHD 1,2 . Interleukins (ILs) are inflammatory cytokines involved in pro‐inflammatory and anti‐inflammatory responses through interactions with a variety of receptors, such as Toll‐like receptors (TLRs) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is a critical driver at all stages of AS, with chemokines, pro-inflammatory cytokines, adhesion molecules, and inflammatory signaling pathways ( 5 ) playing pivotal roles. The NF-κB signaling pathway, in particular, promotes AS by increasing the production of pro-inflammatory cytokines and chemokines such as IL-6, IL-1, Intercellular Adhesion Molecule-1 (ICAM-1), Vascular Cell Adhesion Molecule-1 (VCAM-1), and TNF-α.…”
Section: Immuno-modulatory Features Of Baicalin In Asmentioning
confidence: 99%